2019
DOI: 10.1097/meg.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio is independently associated with inflammatory activity and fibrosis grade in nonalcoholic fatty liver disease

Abstract: Background and aim The progression of nonalcoholic fatty liver disease (NAFLD) to nonalcoholic steatohepatitis (NASH) is believed to be the driver for future development of fibrosis and cirrhosis. Nevertheless, there remains a lack of noninvasive methods for the diagnosis of NASH. The aim of the present study was to determine the role of neutrophil-to-lymphocyte ratio (NLR) in predicting histological severity in NAFLD. Patients and methods We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 24 publications
4
36
0
Order By: Relevance
“…NAFLD patients were found to have a persistent increase of circulating neutrophils and monocytes (Zhang et al, 2018;Khoury et al, 2019). As an extension of these previous findings, we found that mobilization of neutrophils and monocytes in the periphery contributes to the aggravation of hemorrhagic injury in NAFLD mice.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…NAFLD patients were found to have a persistent increase of circulating neutrophils and monocytes (Zhang et al, 2018;Khoury et al, 2019). As an extension of these previous findings, we found that mobilization of neutrophils and monocytes in the periphery contributes to the aggravation of hemorrhagic injury in NAFLD mice.…”
Section: Discussionsupporting
confidence: 85%
“…Among factors that increase the risk of ICH, non-alcoholic fatty liver disease (NAFLD) is a common liver disease that affects up to 30% of the general population (Tsochatzis and Newsome, 2018). NAFLD is characterized by excessive deposition of lipids in liver parenchyma independent of heavy alcohol consumption (Kim et al, 2011;Younossi et al, 2018;Khoury et al, 2019). Accompanying the accumulation of hepatic fat, patients usually display insulin resistance, dyslipidemia, and escalated systemic inflammation (Gluchowski et al, 2017;Fiorucci et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of Fig. 1 Receiver operating characteristic curve analysis for NLR for prognostic value for PSI studies have shown that higher NLR might be an independent predictor of clinical outcome in a variety of diseases, including malignant tumors, acute respiratory distress syndrome, fibrotic liver disease and cardiovascular diseases [29][30][31][32]. At present, it has been paid more attention in the research of neurovascular diseases [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…NLR was described to be a prognostic factor in many liver diseases. In non-alcoholic fatty liver disease, NLR was associated with inflammatory activity and different histological fibrotic grades[ 11 - 15 ]. In chronic viral hepatitis B and C, NLR predicted response to anti-viral therapy[ 16 - 21 ].…”
Section: Introductionmentioning
confidence: 99%